Laboratory and Centrifuge Model Tests on Influence of Swelling Rock with Drying-Wetting Cycles on Stability of Canal Slope - Chen Zhang; Zheng-yin Cai; Ying-hao Huang; Hao Chen (Advances in Civil Engineering)
This study focused on the swelling behavior of swelling rock from canal basement under multiple drying-wetting (D-W) cycles. A series of laboratory tests were conducted on a swelling rock, with the cracking and strength behaviors investigated. By using image-processing technique, the crack patterns were described, and then quantitatively analyzed on the basis of the fractal dimension. The experimental data indicated that swelling ability, including cracking level, fractal dimension, and strength, decrease with increasing drying and wetting cycle. On this basis, a series of centrifuge model simulations for simulating slope failure by drying-wetting cycles were performed, where the drying process was achieved by heat bulbs. The monitoring results suggested that a global slope failure has occurred after total cycle of 4th corresponding to 4 years. Due to the development of surface cracking, the infiltration in the slope was severe and nonuniform in space and time. Meanwhile, the failure mechanism of soft rock slope induced by D-W was discussed.